2015
DOI: 10.1111/aogs.12553
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid erythropoietin and neonatal outcome in pregnancies complicated by intrauterine growth restriction before 34 gestational weeks

Abstract: High amniotic fluid erythropoietin concentrations are associated with decreased umbilical artery pH and base excess and with adverse neonatal outcome in pregnancies complicated by intrauterine growth restriction before 34 gestational weeks. In selected pregnancies complicated by intrauterine growth restriction, determining amniotic fluid erythropoietin could be a useful additional tool in fetal surveillance and possibly in optimizing timing of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In addition, EPO decreases both autophagy and apoptosis via the Akt/mTOR signaling pathway and the MAPK/ ERK pathway, and thus it reduces intestinal mucosa injury from inflammation [11]. Studies also indicate that EPO reduces the occurrence of NEC in mice and rats by inhibiting the lipid peroxidation mediated by oxygen-free radicals [29] and the excessive production of nitric oxide [9,30,31], both of which are associated with the pathogenesis of NEC. In infants, rhEPO (200 IU/kg twice a week for a total of 1 week) reduced neonatal NEC injury by reducing inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EPO decreases both autophagy and apoptosis via the Akt/mTOR signaling pathway and the MAPK/ ERK pathway, and thus it reduces intestinal mucosa injury from inflammation [11]. Studies also indicate that EPO reduces the occurrence of NEC in mice and rats by inhibiting the lipid peroxidation mediated by oxygen-free radicals [29] and the excessive production of nitric oxide [9,30,31], both of which are associated with the pathogenesis of NEC. In infants, rhEPO (200 IU/kg twice a week for a total of 1 week) reduced neonatal NEC injury by reducing inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoietinis an erythropoietic hormone that increases Fe use in support of RBC production under conditions of hypoxia. Studies assessing cord blood EPO concentrations in neonates under hypoxic in utero conditions (including pre-eclampsia, placental dysfunction, maternal smokers, or intrauterine growth restriction) found that cord EPO concentrations were elevated compared to neonates under non-hypoxic conditions (64)(65)(66)(67). Only 1 of these studies concurrently measured Hb concentrations and found that neonates born to mothers who smoked during pregnancy had higher EPO and Hb concentrations compared to non-smokers (67).…”
Section: Discussionmentioning
confidence: 99%
“…EPO is a biomarker of chronic hypoxia, and increased levels can be detected in fetal plasma and amniotic fluid in various pathological pregnancies [7]. An association of high EPO levels during pregnancy and adverse acute neonatal outcome - such as decreased umbilical cord pH, pO 2 , and BE, and increased intensive care unit admission - has also been reported [7,20]. Furthermore, high levels of umbilical plasma EPO at birth are associated with an increased risk for death or abnormal neurological outcome at 2 years of age [8].…”
Section: Discussionmentioning
confidence: 99%